2021
DOI: 10.1002/zaac.202000413
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Isotope fractionation of Zinc in Complexation with Macrocyclic Polyethers

Abstract: Isotope fractionation of Zn was studied via liquid-liquid extraction with aqueous phase of ZnCl 2 /HCl and organic phase of crown ethers(CEs), including benzo15-crown-5(B15C5), benzo-18-crown-6(B18C6) and Dicyclohexano-24-crown-8(DC24C8)/ 1,2-dichloroethane. The isotope enrichment factor (ɛ 66), expressed in permil notation, of the isotope pair 66 ZnÀ 64 Zn was found to be between À 0.24 and À 0.52 % in the order of enrichment: B15C5 � B18C6 > DC24C8. The magnitude of ɛ 66 was well explained by theoretical iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…As the trivalent metal uptake, , V­(III) citrates (Figure k,m) and photosiderofore (Figure n) were computed by referring to the Fe­(III) case . To investigate the divalent metal uptake, the V IV O 2+ –porphyrin complex was computed (Figure r) using the Zn­(II) case, in which Zn 2+ was substituted by V IV O 2+ . The optimized structure showed a square planar structure of V with four N-donors of the porphyrin ring (Figure p).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…As the trivalent metal uptake, , V­(III) citrates (Figure k,m) and photosiderofore (Figure n) were computed by referring to the Fe­(III) case . To investigate the divalent metal uptake, the V IV O 2+ –porphyrin complex was computed (Figure r) using the Zn­(II) case, in which Zn 2+ was substituted by V IV O 2+ . The optimized structure showed a square planar structure of V with four N-donors of the porphyrin ring (Figure p).…”
Section: Resultsmentioning
confidence: 99%
“…In each study, the isotope fractionation experimentally observed was well predicted by theoretical isotope fractionation factors, expressed as beta factors, ln β, obtained by the density functional theory (DFT) method for model molecules related to these systems. Hence, in the present study, we have experimentally determined the isotope fractionation factor, δ 51 V, the ratio of 51 V and 50 V ([ 51 V]/[ 50 V]), for a chemical exchange system with a crown ether, a macrocyclic compound, which engenders isotope fractionation among metals when equilibrated with an aqueous phase. The experimental results were then compared to theoretical calculations determined by employing the DFT method using relevant V model molecules (inorganic species and organometallic species), and we show that the calculations and the experimental work provide comparable results. We then use our calculation method to provide the theoretical isotopic fractionation factor for various V molecules that are relevant to geological and biological environments.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations